2010
DOI: 10.1097/jom.0b013e3181ceff7a
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Air Pollution on Blood Pressure, Blood Lipids, and Blood Sugar: A Population-Based Approach

Abstract: Alterations of atherosclerotic indicators are associated with particulate matter with aerodynamic diameters <10 microm and ozone changes. This might provide a link between air pollution and progression of atherosclerotic cardiovascular diseases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
119
1
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 159 publications
(123 citation statements)
references
References 36 publications
2
119
1
1
Order By: Relevance
“…We are aware of only 3 relevant human studies examining the effect of long-term air pollutants exposure on prevalence of hypertension and arterial BP. 12,26,27 The results of these studies are inconsistent. In the Heinz Nixdorf Recall Study, a population-based prospective cohort in Germany, Fuks et al 27 investigated the cross-sectional association of residential long-term PM 2.5 and PM 10 exposure with arterial BP and hypertension on 4291 participants aged 45 to 75 years, taking short-term variations of PM and long-term road traffic noise exposure into account.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We are aware of only 3 relevant human studies examining the effect of long-term air pollutants exposure on prevalence of hypertension and arterial BP. 12,26,27 The results of these studies are inconsistent. In the Heinz Nixdorf Recall Study, a population-based prospective cohort in Germany, Fuks et al 27 investigated the cross-sectional association of residential long-term PM 2.5 and PM 10 exposure with arterial BP and hypertension on 4291 participants aged 45 to 75 years, taking short-term variations of PM and long-term road traffic noise exposure into account.…”
Section: Discussionmentioning
confidence: 99%
“…6 In recent years, several studies have investigated the shortterm effects of ambient air pollutants in the development of high BP and hypertension among humans, but the results of these studies are inconstant. Evidence from studies conducted in the United States, [7][8][9][10] Brazil, 11 and Taiwan 12 indicated that short-term increases in particulate matter (PM), organic carbon, black carbon, and ozone (O 3 ) air pollution lead to acute but transient increase in arterial BP and hypertension prevalence. However, results from 1 recent study conducted on 9238 nonsmoking adults >30 years of age indicated that shortterm exposure to particles with an aerodynamic diameter ≤10 µm (PM 10 ), sulfur dioxide (SO 2 ), nitrogen dioxides (NO 2 ), CO, and O 3 consistently reduced the systolic BP (SBP) and pulse pressure, whereas the diastolic BP (DBP) was increased by SO 2 , NO 2 , and O 3 .…”
mentioning
confidence: 99%
“…By applying generalized additive models, Secondary analyses of a Taiwanese survey in 2002 demonstrated that increased particulate matter with aerodynamic diameters <10 microm was associated with elevated systolic blood pressure, triglycerides, apolipoprotein B, hemoglobin A1c, and reduced high-density lipoprotein (HDL) cholesterol. Elevated ozone was associated with increased diastolic blood pressure, apolipoprotein B, and hemoglobin A1c (Chuang et al, 2010). Genetic-environment interactions may have a role in this regard (Eisenberg et al, 2010).…”
Section: Impact Of Climate Change and Air Pollution On Dyslipidemia Amentioning
confidence: 99%
“…Therefore, only the variable for the use of any antihypertensive medication (yes/no) was used in the final models. We also studied the possible confounding effect of ozone, because even though the association between ozone and blood pressure is not evident, [29,30] some studies have suggested ozone exposure has an effect on blood pressure [25]. The influence of extreme temperatures on our associations was studied by excluding 2.5% of the hottest and coldest temperatures from the analyses, and we did visual inspection of the linearity of the association between temperature and blood pressure using plots created by penalized spline models, using the generalized additive mixed model (gamm) function in R.…”
Section: Statistical Analysesmentioning
confidence: 99%
“…In this study, we controlled for confounding by black carbon (BC), a marker of combustion particles that has been shown to have an effect on blood pressure in our cohort [23] and elsewhere. [24] Possible confounding by ozone was also studied as a suggestion of an association between ozone and blood pressure has been reported [25].…”
Section: Introductionmentioning
confidence: 99%